Super-gentrification and financialized capitalism: the new frontiers of space-capital in Colina de Santana, Lisbon - Mendes, Luís; Jara, Ana (Pontifícia Universidade Católica de São Paulo, 2018)
The paper focuses on recent changes in the profile of the gentrification process experienced in Lisbon, reinforced in the context of the 2008- 2009 capitalist post-crisis and in the last phase of financialized capitalism. We intend to identify important driving forces in the financialization of the built environment and of the real estate sector that are at the root of the super-gentrification wave that has been occurring in Lisbon in the last decade. These forces allow to maximize a capitalist production of the urban space, aggravating residential segregation, social polarization and spatial injustice in this latest phase of financialized capitalism. The empirical analysis focuses on evidences of a proto-gentrification that seems to be consolidating itself at Colina de Santana, in the historic center of Lisbon.